Bahasa, Tradisi, dan Identitas : Akulturasi Budaya dalam Masyarakat Pandalungan Kabupaten Jember - Kasih, Kartika Bina; Pratiwi, Clara Sinta (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Qomaruddin, Gresik, Indonesia, 2025)
The designation of Jember as an administrative region (afdeling) in 1883 triggered the migration of people from various ethnic groups, particularly Javanese and Madurese communities, who later became the dominant groups in the Tapal Kuda region. The intensive interaction between these groups shaped a distinctive process of cultural acculturation known as Pandalungan culture. This study aims to explore the forms of cultural acculturation between Javanese and Madurese ethnicities in the local arts of Jember. A descriptive qualitative approach was applied using content analysis of various relevant written sources. The findings show that Pandalungan culture has not yet developed into a fully established cultural system, but rather exists as a hybrid cultural expression that continues to evolve. These findings contribute to a deeper understanding of cultural hybridization in folk arts and provide an important basis for preserving local cultural identity and strengthening social harmony in multicultural regions such as Jember.